Preface - Herawan, Tutut (Journal of Information Systems Research and Practice, 2024)
The Volume 6 Issue 1 of JISRP has been available online since 31th March 2024 for the regular issue of March 2024. All articles in this issue (7 original research articles) were authored/co-authored by 27 authors from 5 countries (Malaysia, India, Indonesia, Nigeria, and Philippines).